2023
DOI: 10.1002/cpt.3044
|View full text |Cite
|
Sign up to set email alerts
|

PharmVar Tutorial on CYP2D6 Structural Variation Testing and Recommendations on Reporting

Amy J. Turner,
Charity Nofziger,
Bronwyn E. Ramey
et al.

Abstract: The Pharmacogene Variation Consortium (PharmVar) provides nomenclature for the highly polymorphic human CYP2D6 gene locus and a comprehensive summary of structural variation. CYP2D6 contributes to the metabolism of numerous drugs and thus, genetic variation in its gene impacts drug efficacy and safety. To accurately predict a patient's CYP2D6 phenotype, testing must include structural variants including gene deletions, duplications, hybrid genes, and combinations thereof. This tutorial offers a comprehensive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…Furthermore, we discovered a more than two-fold higher frequency of homozygous carriers (*5/*5) in AFR individuals (0.43%) compared to individuals within the other groups (ranging from 0.11% AMR ancestry to 0.16% EAS ancestry). We observed that whilst the frequency of the *5 allele in the East Asian cohort (5.2%) was iden\cal to that reported in PharmGKB 29 , it was higher than the es\mate from a recent CYP2D6 SV-focused study 3 . Iden$cal gene duplica$ons and mul$plica$ons CYP2D6 duplica\on and mul\plica\on SV events are key to predic\ng the UM category (Supplementary Table 5) and we iden\fied 16,144 carriers (3.4% of the overall popula\on).…”
Section: Cyp2d6 Genotyping and Phenotyping Callingsupporting
confidence: 47%
“…Furthermore, we discovered a more than two-fold higher frequency of homozygous carriers (*5/*5) in AFR individuals (0.43%) compared to individuals within the other groups (ranging from 0.11% AMR ancestry to 0.16% EAS ancestry). We observed that whilst the frequency of the *5 allele in the East Asian cohort (5.2%) was iden\cal to that reported in PharmGKB 29 , it was higher than the es\mate from a recent CYP2D6 SV-focused study 3 . Iden$cal gene duplica$ons and mul$plica$ons CYP2D6 duplica\on and mul\plica\on SV events are key to predic\ng the UM category (Supplementary Table 5) and we iden\fied 16,144 carriers (3.4% of the overall popula\on).…”
Section: Cyp2d6 Genotyping and Phenotyping Callingsupporting
confidence: 47%